(3MGTjI NdjaI SdWGf Ydi eYGde GdCUhds - (3NdjaI SdWGfs ((3eMeO Hf ESeGYjd GdWGQbjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B.. (3Efj bO cJHJ Mjf eWGdYI cJGH eYGde GdOjf ef eUfaGJ GdTjN (B..(3GdMSf Hf GdTjN GdTgjO (B.. (3HYV GdMhGTj Ydjg bGUOG JhVjM ebKGUOg (B..s
(3BNQgG (B:s
.. (3LhRfG chf GdEeGe EP dhde jLR chf GdEeGe ajge dcGf eNGdajge bWYG EPG GfMUQ GdNdGa aj bhdjf adG jJLhR JQLjM GdehGab ddCcKQ (B... (3gPg GdhQbI GdCNjQI ef GdQSGdI GdTQjaIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3hba (B: (3Ydi ChdGO YHO GdcQje ef GdPchQ , SfI (B: 1291 (3g` , Jedc (B: (3GdgGOj Hf GdMSf CHh WGdHs
Keywords: (3CUhd Gdabgs